Haemostatic changes during surgery for primary brain tumours. Issue 3 (1st September 1997) - Goh, Keith Yu-Ching; Tsoi, Wai-Chiu; Feng, Chi-Shun; Wickham, Nicholas; Poon, Wai Sang
Abstract : OBJECTIVE: Primary brain tumours may be associated with coagulation disorders which can pose intraoperative and postoperative management difficulties. The aim was to evaluate the coagulation profile of patients with brain tumours undergoing surgery using thromboelastography (TEG) in combination with simple laboratory tests. METHODS: Fifty adult patients with primary brain tumours larger than 4 cm in maximum diameter and no history of coagulation disorders were studied in a prospective, observational manner over a one year period. Preoperative, intraoperative, and postoperative measurements included haemoglobin concentration, platelet count, prothrombin and partial thromboplastin times, fibrin(ogen) degradation product concentration, D-dimer concentration, and TEG. RESULTS: Eleven patients (22%) had abnormal intraoperative TEGs, of whom six (12%) subsequently developed haematomas requiring surgical evacuation. The coagulopathy seemed to be hyperfibrinolysis in two cases (4%) and disseminated intravascular coagulation in four (8%). There was no preoperative difference in reaction time (R time) for clot formation between the non-haematoma and haematoma groups(mean 11.44 (SD 3.42) v 12.33 (2.50) min, P= 0.46). However, when other preoperative indices were compared, in the non-haematoma group, K time (time to reach a clot amplitude of 20 mm) was shorter (6.72 (2.15) v 10.56 (3.50) min, P=0.001), rate of clot growth (å) was faster (43.67°(7.53) v 27.11° (5.42), P<0.0001) and maximum amplitude of clot strength (MA) was greater (52.64 (7.85) v 40.33 (6.59) mm, P< 0.001). Intraoperatively, R time was significantly shortened in the non-haematoma group, (7.67 (1.78) min, P<0.0001) unlike the haematoma group (10.67 (1.58) minutes, P=0.11). CONCLUSIONS: Although these results indicate a general hypercoagulability during brain tumour surgery, in certain cases, a predisposition towards hypocoagulability may exist even before surgery, detectable only when the physical characteristics of clot formation are studied by TEG. Judicious replacement of clotting factors, platelets, and antifibrinolytic agents should be considered intraoperatively if the TEG is abnormal, without waiting for laboratory test results.